Vitamin B12 deficiency and diabetic neuropathy in patients taking metformin: a cross-sectional study. Issue 10 (October 2019) - Alvarez, Mauricio; Sierra, Oswaldo Rincón; Saavedra, Ginna; Moreno, Sergio
Abstract : Objective: Vitamin B12 deficiency resulting from metformin use has been demonstrated in multiple studies. In this study, we aimed to evaluate the prevalence of vitamin B12 deficiency in patients with chronic metformin use and the relationship between vitamin B12 deficiency and diabetic neuropathy. Methods: A cross-sectional study was conducted with 162 patients. Vitamin B12 levels were measured by chemiluminescence immunoassay. Diabetic neuropathy was evaluated by patient record, nerve conduction and Michigan test for the diagnosis of diabetic neuropathy. Additional data, including demographic characteristics were collected. A linear regression model was used to evaluate variables that correlated with vitamin B12 levels and diabetic neuropathy. Results: Low vitamin B12 levels were found in 7.3% (95% CI: 4.0–12%) of patients. In those with diabetic neuropathy, altered (low and borderline) vitamin B12 level was 64% (95% CI: 47–78%) compared to 17% (95% CI: 10–26%) in patients without diabetic neuropathy (coefficient: −110.8; CI 95%: −165.8, −59.7). Those taking a higher metformin dose had lower levels of vitamin B12 (coefficient: −0.061; CI 95%: −0.09, −0.024). In addition, female patients had higher levels of vitamin B12 compared to men (coefficient: 49.1; CI 95%: 2.3–95). Conclusions: Vitamin B12 deficiency is highly prevalent, especially in patients with diabetic neuropathy. In this study an inverse correlation was found between diabetic neuropathy and the plasma level of vitamin B12. Higher doses of metformin and male sex were factors related to lower levels of vitamin B12.